2017
DOI: 10.1093/ofid/ofx254
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Clinician-Diagnosed Lyme Arthritis, Facial Palsy, Carditis, and Meningitis in Patients From High-Incidence States

Abstract: BackgroundClinical features of Lyme disease (LD) range from localized skin lesions to serious disseminated disease. Information on risk factors for Lyme arthritis, facial palsy, carditis, and meningitis is limited but could facilitate disease recognition and elucidate pathophysiology.MethodsPatients from high-incidence states treated for LD during 2005–2014 were identified in a nationwide insurance claims database using the International Classification of Diseases, Ninth Revision code for LD (088.81), antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
17
1
Order By: Relevance
“…When large forests become fragmented into smaller segments, the number of small vertebrates, such as the white-footed mouse (the primary reservoir for Borrellia species), increases; therefore, more hosts are available for larval tick feeding. As a result, there is a greater chance that these ticks will become carriers of B. burdorferii (62). For military personnel stationed or retired in this location, the risk of exposure to infected ticks is high since routine training drills, other occupational duties, or leisure and recreation often occur in forested areas or short grass prairies (32,34).…”
Section: Discussionmentioning
confidence: 99%
“…When large forests become fragmented into smaller segments, the number of small vertebrates, such as the white-footed mouse (the primary reservoir for Borrellia species), increases; therefore, more hosts are available for larval tick feeding. As a result, there is a greater chance that these ticks will become carriers of B. burdorferii (62). For military personnel stationed or retired in this location, the risk of exposure to infected ticks is high since routine training drills, other occupational duties, or leisure and recreation often occur in forested areas or short grass prairies (32,34).…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of early Lyme disease typically include erythema migrans, fever, chills and headache (Hu, ; Steere, ). Untreated Lyme disease may lead to severe manifestations such as arthritis, facial palsy, meningitis or carditis (Hu, ; Kwit, Nelson, Max, & Mead, ; Steere, , ). Patients presenting with Lyme carditis often require hospitalization for cardiac monitoring; patients undergoing parenteral antibiotic therapy or those with neurologic or arthritic manifestations may also require hospitalization (Hu, ).…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 300,000 cases of Lyme disease are diagnosed each year in the United States (Hinckley et al, ; Nelson et al, ). Previous analyses of claims data focused on patterns of disseminated Lyme disease manifestations and found that a higher proportion of patients with disseminated Lyme disease were male compared to patients with non‐disseminated Lyme disease (Kwit et al, ). Other findings included a higher risk of complete heart block among males 15–29 years of age and a higher risk of meningitis among females 10–14 years of age and males 20–24 years of age (Kwit et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any part of the conducting system could be affected, and conduction blocks of varying degrees (Table 1) are the most common. The incidence of LC varies from 0.2–10% in different reports [2, 17–20]. The actual incidence may be higher.…”
Section: Introductionmentioning
confidence: 99%